2005
DOI: 10.1093/hmg/ddi384
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the peroxisomal ABCD2 transporter in the mouse leads to late-onset ataxia involving mitochondria, Golgi and endoplasmic reticulum damage

Abstract: ATP-binding cassette (ABC) transporters facilitate unidirectional translocation of chemically diverse substances, ranging from peptides to lipids, across cell or organelle membranes. In peroxisomes, a subfamily of four ABC transporters (ABCD1 to ABCD4) has been related to fatty acid transport, because patients with mutations in ABCD1 (ALD gene) suffer from X-linked adrenoleukodystrophy (X-ALD), a disease characterized by an accumulation of very-long-chain fatty acids (VLCFAs). Inactivation in the mouse of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
112
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(123 citation statements)
references
References 54 publications
7
112
0
4
Order By: Relevance
“…To gain further insight into the pathogenesis of NAFLD in the ICD-E mice we therefore examined liver transcription at 6 and 24 hour time points, using expression microarrays. Transcription of two genes involved in fatty acid uptake were up-regulated at 6 hours post-induction (Table 1); Abcd2 , a gene known to be involved in the peroxisomal import of fatty acids [37], and the very low density lipoprotein receptor ( Vldlr ) [38]. It is also interesting to note that a previous report has indicated that Abcd 2 suppresses transcription of the fatty acyl chain elongase Elovl3 and this was supported by our data at all time points [39].…”
Section: Resultsmentioning
confidence: 99%
“…To gain further insight into the pathogenesis of NAFLD in the ICD-E mice we therefore examined liver transcription at 6 and 24 hour time points, using expression microarrays. Transcription of two genes involved in fatty acid uptake were up-regulated at 6 hours post-induction (Table 1); Abcd2 , a gene known to be involved in the peroxisomal import of fatty acids [37], and the very low density lipoprotein receptor ( Vldlr ) [38]. It is also interesting to note that a previous report has indicated that Abcd 2 suppresses transcription of the fatty acyl chain elongase Elovl3 and this was supported by our data at all time points [39].…”
Section: Resultsmentioning
confidence: 99%
“…The Abcd1 − /Abcd2 −/− mice, compared with the Abcd1 -mice, display greater VLCFA accumulation in the spinal cord, 19 higher levels of oxidative damage to proteins, 20 and a more severe AMN-like pathology with an earlier onset at 12 months of age. 19,67 It is worth mentioning that to date, no disease-causative role for ABCD2 has been found, although its absence provokes a partially overlapping fatty acid pattern when compared with the ABCD1-dependent biochemical phenotype. 68,69 We assessed the clinical signs of AMN in these double Abcd1 − / Abcd2 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…The sections were stained with hematoxylin and eosin and Sudan black, or processed for immunohistochemistry to rabbit anti-Iba1: dilution 1/1000 (019-19741 (Wako Pure Chemicals Industries, Ltd., Osaka, Japan)); rabbit anti-glial fibrillary acidic protein (GFAP): dilution 1/300 (Z-0334 (Dako)); mouse anti-synaptophysin: dilution 1/500 (SYNAP--299-L-CE (Leica Biosystems, Nussloch, Germany)); rabbit anti-amyloid precursor protein (APP): dilution 1/100 (AHP538 (AbD Serotec, Oxford, UK)); mouse anticytochrome c: dilution 1/100 (55643 (BD Biosciences Pharmingen, San Diego, CA, USA)); mouse anti-neurofilament H non-phosphorylated (SMI32): dilution 1/3000 (SMI-32P (Covance Antibody, BioLegend, Dedham, MA, USA)); rabbit anti-MDA: dilution 1/1000. 21,24,67 The mounting medium used for the acquisitions of the images was DPX. Images were acquired with Olympus BX51 microscope (UPlan FL N 20 × /0.50 Ph1) (Olympus Corporation, Tokyo, Japan) connected to a Olympus DP71 camera and Cell^B software (Olympus Corporation).…”
Section: Discussionmentioning
confidence: 99%
“…ABCD2 and ABCD3 can compensate for ␤-oxidation defects in X-ALD fibroblasts when overexpressed (42). Recently, we (12,47) reported a functional overlap between ABCD1 and ABCD2 transporters on the metabolism of VLCFA in vivo, as concluded from observations in mouse models in which either Abcd1 and/or Abcd2 was disrupted or overexpressed. However, the differences in sequence, expression patterns (62), and phenotype of these mice suggest specific roles for ABCD2 in fatty acid homeostasis.…”
mentioning
confidence: 86%
“…However, the differences in sequence, expression patterns (62), and phenotype of these mice suggest specific roles for ABCD2 in fatty acid homeostasis. Indeed, Abcd2 Ϫ/Ϫ mice exhibit a lateonset cerebellar and sensory ataxia, areflexia, loss of cerebellar Purkinje cells, and dorsal root ganglia cell degeneration (12), together with oxidative damage in adrenal gland (35). These pathological features, not shared with Abcd1 null mice, might indicate that substrate specificity occurs in spite of a certain degree of overlap on C26:0 and/or that expression patterns at the cellular level are different between both and so are the cell types most sensitive to demise upon loss of function (62).…”
mentioning
confidence: 99%